2005
DOI: 10.1042/bj20050457
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the hydrophobic strand in the A–B loop of leptin as major binding site III: implications for large-scale preparation of potent recombinant human and ovine leptin antagonists

Abstract: Interaction of leptin with its receptors resembles that of interleukin-6 and granulocyte colony-stimulating factor, which interact with their receptors through binding sites I-III. Site III plays a pivotal role in receptors' dimerization or tetramerization and subsequent activation. Leptin's site III also mediates the formation of an active multimeric complex through its interaction with the IGD (immunoglobulin-like domain) of LEPRs (leptin receptors). Using a sensitive hydrophobic cluster analysis of leptin's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
77
0
5

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 91 publications
(85 citation statements)
references
References 31 publications
3
77
0
5
Order By: Relevance
“…We previously reported the development of leptin antagonists in four animal species (15,16) by alanine mutagenesis of residues LDF (amino acids 39 -41) or LDFI (amino acids 39 -42). Using mouse leptin antagonist (MLA), 4 we demonstrated that inhibition of leptin signaling is beneficial in several mouse models of fibrosis and inflammation (9,10).…”
mentioning
confidence: 99%
“…We previously reported the development of leptin antagonists in four animal species (15,16) by alanine mutagenesis of residues LDF (amino acids 39 -41) or LDFI (amino acids 39 -42). Using mouse leptin antagonist (MLA), 4 we demonstrated that inhibition of leptin signaling is beneficial in several mouse models of fibrosis and inflammation (9,10).…”
mentioning
confidence: 99%
“…Treatments were chronic ICV infusion of artificial cerebrospinal fluid (aCSF; 150 mM NaCl, 1.2 mM CaCl 2 , 1 mM MgCl 2 , 2.8 mM KCl), ovine leptin (4 µg/h; treatment designated L) or the combination of ovine leptin (4 µg/h) and its mutant version OLA (40 µg/h; treatment designated L + OLA). OLA and leptin have a similar affinity for the leptin receptor (Niv-Spector et al, 2005). Accordingly, in the case of the L + OLA treatment, the OLA infusion rate was 10 times higher than that of leptin to ensure OLA predominance at the receptor.…”
Section: Methodsmentioning
confidence: 99%
“…The OLA mutant has the same exact sequence as ovine leptin except for alanine substitution mutations of amino acids 39 to 41. Ovine leptin and OLA were produced in a bacterial expression system, refolded and purified to homogeneity as previously described (Niv-Spector et al, 2005). All proteins were dissolved in aCSF, with each ICV treatment delivered as a 100 µL/h continuous infusion using a syringe pump (model SE 400; Vial Medical, Grenoble, France).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations